Development of a two-tube multiplex real-time fluorescent PCR for the simultaneous differentiation of the mpox virus clades and the A.1, B.1 and C.1 lineages within clade IIb - Fan, Guohao; Lin, Yuanlong; Yang, Liuqing; Peng, Yun; Ou, Guanyong; Qian, Qi; Lai, Dongmei; Wang, Fuxiang; Liu, Yingxia; Yang, Yang (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundNew clades and lineages emerged with the globally prevalent of Mpox virus (MPXV), accompanied by changing clinical symptoms, pathogenesis and transmission dynamics in associated with specific clades and lineages.MethodsHere, we developed a two tube multiplex real-time fluorescent quantitative PCR (mrt-qPCR) assay for simultaneous differentiation of MPXV clades Ia, Ib, II, and innovative binding lock nucleic acid (LNA) probes to detect A.1, B.1 and C.1 lineages within the clade IIb.ResultsThe assay demonstrated high sensitivity (33–69 copies/reaction) and specificity with expected linearity and stability. The intra-assay and intre-assay coefficients of variations (CV) were below the acceptable threshold of 5%, and the mrt-qPCR method has good stability and reproducibility. Clinical validation using 109 qPCR positive, 1 clade IIb B.1 virus strain and 15 negative specimens revealed 100% concordance for the differentiation of the three clade II and 97.60% for the differentiation the three lineages. The two tube multi-test system streamlined workflows, enabling efficient screening of diverse clinical samples (swabs from skin lessions, oropharynx and rectum, saliva and plasma).ConclusionsWe have established a two-tube multiplex qPCR method for detecting different clades and lineages of the MPXV. This method addresses the issue of false-negative detection of MPXV clade Ib caused by gene fragment deletion, and has also enabled the development of a rapid detection approach for the predominantly circulating clade IIb (including lineages A.1, B.1, and C.1). This cost-effective assay provides an important tool for accurate diagnosis, typing and epidemiological surveillance of MPXV.